ANALISA PERFORMA HEAT EXCHANGER TIPE SHELL AND TUBE PADA PROSES PENDINGINAN PELUMAS SAG MILL DI AREA GRINDING CONCENTRATOR AREA 130 PT. AMMAN MINERAL NUSA TENGGARA - I Wayan Joniarta; Wahyudi Santosa; Made Wijana (Jurusan Teknik Mesin dan Industri, Fakultas Teknik, Universitas Mataram, 2023)
In the industrial world, the use of heat exchanger has an important role in helping the production process, especially in PT. Amman Mineral Nusa Tengggara. Heat exchanger which is used in various production process installations is basically a place to exchange energy in the from of heat from one fluid source to another. In the operation of a heat exchanger on a Semi Autogenous (SAG) mill this process is called oil conditioning, namely oil conditioning involving cooling and filtration in oil to coll the lubricant on the bearing SAG mill. This shell and tube type heat exchanger greatly influences the entire set of processes, because the operation caused by mechanical or operational failure can stop the operation of the unit. In this study do a comparison between the design specifications with the results of observations in the field in the morning and evening. Observations for 5 times were then analyzed using heat transfer to determine thermal load, heat transfer rate, heat transfer coefficient, LMTD, TDC. The results of these calculations can show that the heat exchanger in the morning has better performance. This is evident from its high effectiveness in the morning. However, the heat exchanger damages the leakage of the tube resulting in the mixing of oil with water and impurities from the cooling water quality from poor water flow can cause a decrease in performance on the heat exchanger.